Optimizing water resource management in tropical drought-prone regions through hybrid MCDM techniques: A water-stress mapping approach - Suman Mukherjee; Suman Paul; Subhasis Bhattacharya; Aznarul Islam; Sadik Mahammad; Edris Alam (Journal of Hydrology: Regional Studies)
Study region: Purulia district of Chotonagpur region, Eastern India. Study focus: Mapping regional water-stress due to climate change and human interventions received less attention in the previous works. Therefore, the eastern Chotonagpur region, one of the drought-prone areas of the world with mounting temperature and heat waves in the summer, is examined in the context of uncertainty of rainfall and a precarious agrarian economy. Groundwater resources of the region are also limited due to the composition of hard rock geology and the low yield prospects of hard aquifers. This study intends to figure out the overall relative water-stress in a comprehensive way using hybrid MCDM. New hydrological insights: Thirty-three indicators-based thematic layers under topographical, hydrological, environmental, hydro-meteorological, and socio-demographic dimensions with integrated CRITIC (quantitative), DEMATEL (qualitative), VIKOR and TOPSIS produced four relative water-stress maps of the study region. The DEMATEL-TOPSIS model was found to be the best-fit method as it produced better accuracy compared to the other models (CRITIC-TOPSIS, CRITIC-VIKOR, and DEMATEL-VIKOR) with AUC of 0.835 and accuracy of 0.881. Though the entire region experiences water-stress, the central part and some portions of the northeastern community development blocks exhibit higher intensity. Our study advances the ability of water-stress area identification, applying integrated methods and comprehensive geospatial datasets in a water-scarce region.